2018
DOI: 10.1159/000493952
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression Profile and Analysis of Their Potential Function in Psoriasis

Abstract: Background/Aims: Circular RNAs (circRNAs) are evolutionary conserved circular non-coding RNAs that play a role in several diseases by sequestering (sponging) microRNAs (miRNAs). However, their role in psoriasis remains unclear. In the present study, we investigated the expression of circRNAs and analyzed their potential functions in psoriasis. Methods: The SBC human ceRNA array V1.0 was used to analyze circRNA expression in psoriatic lesions and normal healthy skin tissues. Functional analyses were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
(36 reference statements)
1
43
0
Order By: Relevance
“…Circular RNAs (circRNAs) are a new class of noncoding RNA molecules that extensively exist in the cytoplasm of eukaryotic cells . It is known that circRNAs are different from linear RNAs, lacking 5′ to 3′ polarity and polyadenylated tail and having great stability . CircRNAs have a variety of functions, such as regulating splicing and transcription, binding proteins, and transporting RNAs .…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a new class of noncoding RNA molecules that extensively exist in the cytoplasm of eukaryotic cells . It is known that circRNAs are different from linear RNAs, lacking 5′ to 3′ polarity and polyadenylated tail and having great stability . CircRNAs have a variety of functions, such as regulating splicing and transcription, binding proteins, and transporting RNAs .…”
Section: Introductionmentioning
confidence: 99%
“…The authors found almost 5,000 differentially expressed circRNAs of which the majority was upregulated in psoriasis. Six differentially expressed circRNAs were then selected for verification by RT-qPCR, but only one of these, hsa_circ_0061012, could be verified [46]. Again, we did not detect this circRNA and could not examine if it is differentially expressed in our samples.…”
Section: Discussionmentioning
confidence: 98%
“…Another recent study profiled circRNA expression in three psoriatic lesions and three normal healthy skin tissues [46]. The RNA from these samples was amplified prior to microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that hsa‐miR‐6817‐5p was closely associated with hsa_circ_0061012, which was up‐regulated in psoriasis significantly. Psoriasis was related well to the regulation of NF‐kappaB, whose activity could be weakened by NELL‐1 …”
Section: Discussionmentioning
confidence: 99%